Evaluation of Vitamin D3 metabolite (25-OH Vit D3), Neurotransmitter (ACh), and the Expression of Proinflammatory Cytokines (IL-6 and TNF-α) in Tissue Homogenate after Administration of Biofield Energy Healing-based Novel Proprietary Test Formulation and Biofield Treatment per se to the Animals in Vitamin D3 Deficiency Diet (VDD)-induced Sprague Dawley Rats - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Snehasis Jana (Journal of Neurological Research And Therapy, 2021)
A novel proprietary test formulation was designed which included minerals, vitamins, β-carotene, cannabidiol isolate,and Panax ginseng extract. This present study was evaluated the impact of the Trivedi Effect® on novel proprietary test formulation in male Sprague Dawley rats, fed with vitamin D3 deficiency diet (VDD). The novel test formulation was divided into two parts; one part was defined as untreated test formulation, while the other part was defined as the Biofield Energy Treated sample, which received the Biofield Energy Healing Treatment by renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. The level of 25-OH Vit. D3 was measured in brain homogenate, which was found to be increased by 20.13%, 24.12%, 45.86%, 14.79%, and 29.96% in the G5 group treated with Biofield Treated test formulation, Biofield Energy Treatment per se to the animals (G6), 15 days pre-treatment of Biofield Energy Treated test formulation (G7), Biofield Energy Treatment per se plus Biofield Energy Treated test formulation from day -15 (G8), and untreated test formulation to the Biofield Energy Treated animals (G9) groups respectively, as compared with the disease control (G2) group. Brain acetylcholine (ACh) level was increased by 61.33% in the G7 group as compared with the untreated test formulation (G4) group. The expression of interleukin-6 (IL-6) was significantly reduced by 43.44% (p≤0.01), 30.93%, 21.42%, 45.99% (p≤0.01), and 60.85% (p≤0.01), respectively as compared with the G4. Lung pro-inflammatory cytokine tumor necrosis factor alpha (TNF-α) level was significantly reduced in the G5, G6, G7, and G8 by 24.86%, 32.55% (p≤0.01), 30.12% (p≤0.01), and 42.69% (p≤0.01), respectively, as compared with the G4 group. Altogether, the Biofield Treated test formulation and/or per se treatment to the animals significantly improved the levels of active form of vitamin D3 metabolite (25-OH Vit D3) and neurotransmitter (ACh); consequently significantly lowered the expression of proinflammatory cytokines (IL-6 and TNF-α). Therefore, the energized test formulation or per se treatment could be effectively useful against neuronal damage and inflammation for the management of brain disorders such as Alzheimer’s disease, dementias, brain cancer, epilepsy and other seizure disorders, mental disorders, and Parkinson’s. Thus, the results showed a significant slowdown of disease progression and all other disease-related complications/symptoms in the preventive Biofield Energy Treatment group per se and the Biofield Energy Treated Test formulation groups (viz. G6, G7, G8, and G9) as compared to the disease control group.
Keywords: Vitamin D3 Deficiency